EARLY BYZANTINE POTTERY WORKSHOPS IN OLYMPIA - Schauer, Christa (Rei Cretariae Romanae Fautorum Acta, 2024)
Between 1987 and 1991, excavations of the German Archaeological Institute in Olympia under the direction of Ulrich Sinn uncovered north of the Prytaneion a building complex with architectural phases from the Hellenistic to the Early Byzantine period. In Hellenistic and Roman Imperial times, it contributed to the infrastructure of the Panhellenic sanctuary, with possibly multifunctional rooms around a court at first and a Roman peristyle with elaborate mosaic pavements, later. From Hellenistic times on, the building also comprised bathing facilities. The initial Hellenistic circular bath was replaced at different stages with a Roman water basin and an annex with Roman thermae. The Christian inhabitants of the Early Byzantine settlement reused the then semi-destructed building.